Analisis Formulasi Kebijakan Penanggulangan Pandemi Covid-19 di Indonesia - Debby Putri Pratama; Roni Ekha Putera; Hendri Koeswara (Jurnal Administrasi Publik, 2022)
The Covid-19 virus has spread in Indonesia since March 2020. The policies taken by the government and the background of the formulation of these policies are interesting to discuss. This research aims to describe the policy formulations that taken related to the handling of Covid-19. The research method used in this research is a qualitative method. The theory used in this research is the theory of policy formulation model by Thomas R Dye. The results of this study are in the selection of policies to overcome the pandemic, the government uses the Elite Model where this model describes public policy making in the form of a pyramid, where the public is at the lowest level, the elite is at the top of the pyramid and the internal actors of the government's public policy-making bureaucracy are in the middle between society and elite. This can be seen from the selection of PSBB and PPKM as a way to deal with Covid-19 rather than regional quarantine or lockdown.